PENGAWETAN KAYU TISUK (Hibiscus macrophyllus Roxb.) MELALUI RENDAMAN DINGIN DENGAN BAHAN PENGAWET BORIC ACID EQUIVALENT - Endah Suhaendah; M. Siarudin (BRIN Publishing, 2014)
Tisuk (Hibiscus macrophyllus Roxb.) is one of fast growing tree species widely planted in private forest mainly in Java Island. However one of the weaknesses of tisuk wood is the low durability which is categorized as durability class of III/IV. This paper studies the durability improvement of tisuk wood using Boric Acid Equivalent (BAE) with cold immersion method. The tisuk wood samples were taken from a private forest in Sukamulih Village, Sariwangi Sub-district, Tasikmalaya Regency. The treatments applied were wood thickness (thickness of 2.5 cm, 5 cm, 7.5 cm and 10 cm); immersion time (3 days, 5 days and 7 days); and two preservative concentration (5% and 10%). Each treatment was replicated in 10 specimens (total of 240 specimens). The parameters measured were the retention and penetration of preservative solutions. The analysis of variance shows that the retention of the preservative solutions was significantly different for the wood thickness treatment but it was not significant for other treatments (immersion time and preservative concentration). Meanwhile, the penetration of the preservative solutions was not significantly different for all of the treatments. The retention and penetration of the preservative solution fulfilled the minimum standard required by Indonesian National Standard for wood preservation in all treatments. Based on the analysis, the wood preservation method recommended for tisuk wood using boron and boric acid solutions is 3 days of duration of immersion with concentration of 5% for all of wood thickness treatments (2.5 cm, 5 cm, 7.5 cm and 10 cm).